PREFERENCES OF DRINKING WATER IN MERAM DISTRICT - Boyraz, Yusuf Kenan; Demir, Lütfi Saltuk; Eken, Kübra; Tabara, Muhammed Fatih; Evci, Reyhan; Durduran, Yasemin; Uyar, Mehmet; Şahin, Tahir Kemal (LIFE: International Journal of Health and Life-Sciences, 2017)
In this study, it was aimed to determine the preferences of drinking water for the people aged 18 years and old in Meram district. This cross-sectional study is conducted in Konya province Meram district between dates April 1-June 1, 2016. Sample size is calculated as 810 people by G-Power 3.1.9.2 sample volume calculation program. A questionnaire prepared by the researcher was given to the participants. Questionnaires were giving to the participants during face-to-face interview. Analyzes of the data were studied in the IBM SPSS 24.0 program on the computer. 514 women (63.5%) and 296 men (36.5%) participated in the study. Daily water consumption average is founded as 1.40 ± 0.81 L. It is found that %9,5 (77) of the participants choose water purifier equipment, %19,4 of the participants (157) choose tap water, %22,0 of participants choose packaged water, %49,1 of participants choose fresh water fountain as drinking water. It is determined that 653 participants (80.6%) who did not prefer tap water didn’t prefer it because of these factors: from the taste and odor problem, from limy water, were thought water was dirty, because of the habit, of them was disturbed by chlorinated water.